Identifikasi dan Uji Aktivitas Antimikrobia Bakteri Asam Laktat dari Fermentasi Singkong (Gatot) terhadap Bacillus cereus dan Aspergillus flavus - Febriana, Maria Hesty; Purwijantiningsih, Ekawati; Yuda, Pramana (Universitas Atma Jaya Yogyakarta, 2021)
Gatot is a traditional food from fermented cassava. Lactic acid bacteria (LAB) can be found in fermented cassava food, gatot. Lactic acid bacteria can produce an antimicrobial compound for inhibiting pathogen microorganism. The aim of this research were isolation and identification LAB from gatot and antimicrobial activity test against Bacillus cereus and Aspergillus flavus. Three isolates from raw gatot and three isolates from cooked gatot used in this research. Isolation of LAB was conducted using pour plate method, purification is conducted by streak plate method, the antimicrobial test was conducted by agar well diffusion and molecular identification was conducted by PCR colony method using LABFw and R16RDNA-1492bac primer. Lactic acid bacteria from cooked gatot identified as Enterococcus sp. FTBUAJY04, Enterococcus sp. FTBUAJY05, Enterococcus sp. FTBUAJY06, while LAB from raw gatot identified as Lactococcus lactis strain FTBUAJY01, Lactococcus lactis strain FTBUAJY02 dan Lactococcus lactis strain FTBUAJY03. The results obtained from the inhibition zone test showed that all isolates were able to inhibit the growth of B. cereus and A. flavus. Â The greatest inhibition zone against B. cereus was shown by LAB Gt5 supernatant or L. lactis supernatant strain FTBUAJY02 of 1.87 Â± 0.67 cm2, while the results of the greatest inhibition zone against A. flavus was LAB Gt6 supernatant or L. lactis supernatant strain FTBUAJY03 of 3.83 Â± 0.73 cm2.